What they didn't teach you in art school What you need to know to survive as an artist - Davis, Rosalind; Tilley, Annabel
"You've been to art school, you've done the work,and you've got the talent- but do you know how to make a success out of it? Turning your passion into a career in the fiercely competitive art world means becoming your own finance, business, and marketing manager- as well as researcher, curator, and administrator.